PERGESERAN MAKNA TRADISI MINUM AIR RAJHA’AN PADA HARI REBUH BEKKASAN - Urwatul Wusko (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
The tradition of drinking Rajha'an water on the day of Rebuh Bekkasan is one of the many traditions that the Javanese still preserve. Rebuh Bekkasan tradition is a ritual performed on the last Wednesday in the month of Shafar to ask for safety and reject 'balance.' However, with the development of education, the traditions that become the order of social life have experienced a shift under changes in other aspects of socio-cultural life caused by factors from outside and within the community itself. This research is a type of qualitative research using a phenomenological approach. Data collection techniques used the observation, interviews and documentation. The data obtained were analyzed using qualitative descriptive analysis with the interactive model of Milles and Huberman. Meanwhile, the validity of the data used the source and technical triangulation. The results of the study show that: majority of students practice the tradition of drinking Rajha'an water, the goal is not to ask for safety and refuse reinforcements as the original goal of the tradition and santri carry out the tradition only to obey the rules of the pesantren and want to expect blessings from the kiai so that their knowledge is blessed and beneficial. Internal factors that cause a shift in the meaning of tradition, among others, are: the development of educational science in Pondok Pesantren, there is not notification and coordination between the management and the students before implementing the tradition and changes in the implementation of traditions differ from the previous year. And external factors is: the student's ignorance of the Rebuh Bekkasan tradition because they had never done this tradition at home before, and the increasing of new students who do not understand the background and meaning of tradition.